Into the matrix: current methods for mitochondrial translation studies. (26th January 2022) - Apostolopoulos, Antonios; Iwasaki, Shintaro
Abstract: In addition to the cytoplasmic translation system, eukaryotic cells house additional protein synthesis machinery in mitochondria. The importance of this in organello translation is exemplified by clinical pathologies associated with mutations in mitochondrial translation factors. Although a detailed understanding of mitochondrial translation has long been awaited, quantitative, comprehensive and spatiotemporal measurements have posed analytic challenges. The recent development of novel approaches for studying mitochondrial protein synthesis has overcome these issues and expands our understanding of the unique translation system. Here, we review the current technologies for the investigation of mitochondrial translation and the insights provided by their application. Graphical Abstract: